School Policy in Supporting Indonesia Smart Program at Private Junior High School (SMP) of Santo Gabriel Sekadau - Neli Neli; M. Syukri; M. Chiar (JETL (Journal of Education, Teaching and Learning), 2019)
The purpose of this study is to obtain information about school policies in supporting PIP which is focused on the process of determining prospective PIP recipients, strategies implemented by the principal, procedures for implementing PIP policies, forms of PIP policies and constraints. With a qualitative approach, this research was compiled using interview data and document data. Data analysis uses data reduction, data presentation, and conclusion. This study found that the school policy in supporting PIP was in the form of (1) The process of determining prospective PIP recipients, namely the establishment of a PIP responsible committee equipped with assignments and referring to technical guidelines. Supporting documents for the determination of prospective PIP recipients in the form of new student admission forms, photocopies of COWs, photocopies of PIP cards, photocopies of KKS, and PKH; (2) The strategy carried out by the school principal in supporting PIP conducts socialization, proposing students who are eligible to receive PIP; and provide socialization / direction to students receiving PIP; (3) Procedures for implementing PIP policies are guided by technical guidelines; (4) In the form of the PIP policy in Santo Gabriel's private junior high school, the PIP funds were collected collectively by the principal, the PIP funds received were intended to pay for student re-registration, school fees, and books. The school submits a written report to the District Education Office regarding the realization and distribution of PIP funds; (5) Internal barriers in supporting PIP, namely: (a) Students do not understand PIP; (b) New student admission forms are incomplete; and (c) The committee has difficulty in determining eligible students to be submitted as candidates for PIP recipients. Whereas external barriers, namely student data sent centrally when disbursing some students are not all realized.